Quality of life of workers with disabilities in readymade garments factories in Bangladesh - Rahman, Md. Habibur; Habibur Rahman, Mohammad; Akter Kakuli, Samena; Kabir, Md. Feroz; Moniruzzaman, Sk.; Hossain, Md. Sazzad; Subahan, Sanjida (International Journal of Research in Medical Sciences, 2023)
Background: Bangladesh’s readymade garment (RMG) sector has developed as a major employer for individuals with disabilities. The number of workers with disabilities in Bangladesh’s RMG industry has grown over the past few years. In Bangladesh, there has no statistics about the quality of life of workers with disabilities after their employment, especially after training-based employment support. Therefore, the researcher is interested to find out the quality of life of workers with disabilities in readymade garments factories in Bangladesh that will determine satisfaction over their life in different aspects. The objectives of this paper were to find out the health-related quality of life and overall satisfaction with life among workers with disabilities in the readymade garment sector in Bangladesh. Methods: This study used a cross-sectional design and recruited 102 participants with disabilities from various Bangladeshi garment factories who ranged up to 18 years by convenient sampling. The WHOQOL questionnaires were used for data collection through a combination of telephone and in-person interviews. Descriptive statistics were used for the data analysis. Results: Among the total participants 63% of them were women and 37% were men. The results revealed that education and job status significantly impacted on QOL. The majority of participants did not need any assistive devices; most of the participants resided in semi-urban areas, and physical disabilities predominated among them. On the other hand, most of the participants reported their quality of life as neither poor nor good but they were satisfied with health-related QOL. Conclusions: QOL is a vast aspect of every human being. This study finally concluded the overall QOL of maximum Workers with Disabilities in Readymade Garments Factories in Bangladesh was just average and most of them were satisfied with their health-related QOL.